Hubungan antara Kualitas Pribadi Guru BK dengan Kepuasan Siswa terhadap Layanan Konseling Individual di SMP Negeri 5 Kupang - Vebronia Marieta Kewa Benikakan; Lolang Maria Masi; Katharina E.P Korohama (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
The phenomenon of student satisfaction with individual counseling services at school still shows variation. Some students feel dissatisfied because they think that BK teachers have not fully displayed empathy, warmth, and sensitivity in helping them. This condition has an impact on the reduced interest of students to take advantage of counseling services. This study aims to find out the description of the personal quality of BK teachers, the level of student satisfaction with individual counseling services, and the relationship between the two at SMP Negeri 5 Kupang. The research method used is a quantitative approach with a correlational design. The research sample amounted to 66 students in grades VII and VIII who were selected by purposive sampling technique. Data was collected using a Likert scale questionnaire, then analyzed with descriptive statistics and product moment correlation tests. The results showed that the personal quality of BK teachers was in the medium category (72.7%) and student satisfaction with individual counseling services was also in the medium category (65.2%). The correlation test showed a positive and significant relationship between the personal quality of BK teachers and student satisfaction (r = 0.242 > r table). Thus, it can be concluded that the personal qualities of BK teachers play an important role in increasing student satisfaction with individual counseling services. Therefore, improving the personal quality of BK teachers needs to be a concern in order to improve the quality of counseling guidance services in schools.